Influência da soldagem de revestimento na vida útil de ponteiras sulcadoras de semeadoras adubadoras. - Ferreira, Mauro Fernando (2008)
This work had as objective to analyze alternatives to increase the useful life of the ferrules of hoe opener rods of no-till planters, through the addition of covering welding. It was verified the performance of five welding types, being used covered electrodes and tubular wire, over the extremity of the hoe. The tests were executed in franc-sandy soil characterized physically by its texture, plasticity index, density, and water tenor, as well as the resistance to the penetration. The wearing, the horizontal and vertical force were obtained in intervals of 10,5km to the limit of 52,5km. The results indicated that the witness ferrule has lost in the average of the experiment 38,41% of its initial mass when it traveled 52,5km while the other welded ferrules traveled between 61,0km and 108,7km to reach the same mass reductions. It was observed that the vertical and horizontal forces contributed with 11% and 89%, respectively, of the resulting force in the hoe. With the use of the coverings, it was obtained an increase of the area worked in the sowing, for the largest durability of the tools, between 2,0ha and 13,4ha, in relation to the witness. The theoretical field efficiency was larger when it was used the coverings. The tubular wire increased in 5,1% in relation to the ferrule without covering. Starting from the found results we can conclude that it is possible to increase the useful life of the ferrules of furrow opener rods through the addition of welding material and that the conservation of the geometry of the tools, provides the maintenance of the forces that have action on these ones as well as their functional characteristics.